Prevalence of HIV in syphilis in a tertiary care centre - Sundararaj, Sumithra; Sendurpandian, Devaprabha; Rajakumari, Suganthy R. (International Journal of Research in Dermatology, 2019)
Background: Aim of this study was to determine the prevalence of HIV in syphilis in patients attending the STD clinic in a tertiary care center. Methods: Study was conducted in all new patients attending the STD clinic during the study period of 6 months from June 2012 to November 2012. Clinically suspected cases of syphilis were diagnosed serologically and all the patients were tested for HIV after proper counselling and consent. Results: In a total of 200 new patients attended the STD clinic 47 (23.5%) were diagnosed as syphilis. Majority of the cases (43) were latent syphilis in our study. A total of 77 (38.5%) cases were reactive to HIV. Among the 47 (23.5%) syphilis cases 24 (51%) were reactive to HIV. In the age group of 21-30 years most of the syphilis male (5/6) patients showed HIV reactivity. Conclusions: Seroprevalence of syphilis among other STI was found to be significant. Rising trend in latent syphilis was noted may be due to antenatal checkup, purpose of foreign job and strict blood screening protocols. The prevalence of HIV in syphilis individual was 51% and it was high in the age group of 31-50 when compared to other age group. In the age group of 21-30 most of the males, diagnosed as syphilis were serologically positive for HIV. Hence these sexually active groups were to be targeted for their safe sexual practice to prevent the transmission of HIV.